2013
DOI: 10.1177/1066480713505058
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Marriages in a Community of Pakistan

Abstract: The structuralist and social exchange theorists relate the system of the exchange marriage mainly to socioeconomic interests, the formation of political and social alliances, as well as to the creation of a kinship network. However, they negate the inherited problems of the system of the exchange. This article discloses positive and negative aspects of the exchange and the cycle of social exchange. This study focuses on the notion of adequate social exchange. The study reveals tensions between individual and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Exchange marriages are customarily practiced in the rural areas of Punjab and Sindh provinces. 14,16 Then, parental consanguinity was also observed to be a significant predictor of subject's consanguinity in the present study. This observation supports the notion that consanguinity is a family tradition that is practiced generations after generations.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Exchange marriages are customarily practiced in the rural areas of Punjab and Sindh provinces. 14,16 Then, parental consanguinity was also observed to be a significant predictor of subject's consanguinity in the present study. This observation supports the notion that consanguinity is a family tradition that is practiced generations after generations.…”
Section: Discussionsupporting
confidence: 66%
“…2,7 Consanguinity helps them to settle minor domestic conflicts and social and economic problems. 14 Further, the rate of CU was significantly higher in subjects who had younger age at marriage. The analyses demonstrated that rate of consanguinity gradually declined as the age at marriage delayed.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…This type of marriages is used to control and maintain a balance of power between families and the couples (Naveed & Butt, 2015: 167). The men's behaviour is conditioned through good or abusive treatment extended to his blood relative bride involved in exchange and living in other party's home (Jacoby & Mansuri, 2010, 1806Zaman 2013;Zaman, Zakar, & Sharif 2014). Therefore, it is considered as a double edged sword that cuts both ways (Bhutta et al 2015: 167;Jacoby & Mansuri, 2010, 1813.…”
Section: Literature Reviewmentioning
confidence: 99%